2020
DOI: 10.15294/lc.v15i1.24453
|View full text |Cite
|
Sign up to set email alerts
|

Modality Analysis on the Official Website of Indonesian Tourism

Abstract: Tourism is believed as the primary motivation to improve the economy of a country. In order to attract some tourists to visit tourism destinations in Indonesia, The Ministry of Tourism establishes an official website to share the information regarding the tourism destinations, activities, and attractions. This study is conducted to observe how the official website of Indonesian tourism utilizes modality to present Indonesian tourism discourse. This paper analysed ten destination highlights of the website cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These findings pointed to the strategic linguistic choices that influence teacher-student interactions and the educational environment. The results and findings confirmed the SFL principles that language plays a role in conveying information and constructing interpersonal relationships and organisational structures within classroom discourse (Achugar et al, 2007;Halliday & Matthiessen, 2004;Harnida et al, 2021;Rahmasari & Lauwren, 2020;Sagayadevan & Jeyaraj, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…These findings pointed to the strategic linguistic choices that influence teacher-student interactions and the educational environment. The results and findings confirmed the SFL principles that language plays a role in conveying information and constructing interpersonal relationships and organisational structures within classroom discourse (Achugar et al, 2007;Halliday & Matthiessen, 2004;Harnida et al, 2021;Rahmasari & Lauwren, 2020;Sagayadevan & Jeyaraj, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…Studies on the website have been found in the way Indonesian authenticity, comprising nature, cultural heritage, and cuisine, is presented through various linguistic and visual modes (Arfin Muhammad Salim and Puad Mat Som, 2018;Isti'anah, 2020;Rahmasari and Lauwren, 2020;Salim et al, 2018;Samad et al, 2018). Those studies agreed that Indonesian tourism has various unique selling points described through descriptive verbs, positive adjectives, and declarative sentences.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have paid attention to Indonesian tourism discourse: how the official website of Indonesian tourism reveals the authenticity of nature and culture (Salim et al, 2018), cuisine (Samad, Salim, & Akib, 2018), and the linguistic strategies through modality and language evaluation to present Indonesian physical environment (Isti'anah, 2020;Rahmasari & Lauwren, 2020). They argue that tourism's official website performs as an information source and promotional tool to invite prospective tourists.…”
Section: Introductionmentioning
confidence: 99%